Atividade antimicrobiana e mecanismo de ação de peptídeos sintéticos bioinspirados em JcTI-I, um inibidor de tripsina de Jatropha curcas - Souza, Larissa Alves Lopes de (2023)
In recent years, the increase in microbial resistance has caused concern and represents a serious public health problem, causing thousands of deaths worldwide. Thus, the discovery of new antimicrobial agents to control these resistant microorganisms is urgent. Within this context, antimicrobial peptides, especially synthetic ones, have been highlighted in the control of these infections, using different mechanisms of action. Therefore, the objective of this work was to design and synthesize peptides inspired in the sequence of a purified trypsin inhibitor from Jatropha curcas cake (JcTI-I), which has already shown to be antimicrobial, in addition to investigating its mechanisms of action against different species of yeasts and bacteria. The experimental strategy comprised three sections: Section 1) in silico design and analysis of the peptides, in order to evaluate their physicochemical characteristics as well as predict their antimicrobial activity, Section 2) investigation, in vitro, of the peptides' antimicrobial action mechanisms and Section 3) analyses, in vitro and in silico, to assess the safety of using the peptides. The results revealed that one of the designed peptides, called JcTI-PepI, proved to be highly effective against different species of Candida. JcTI-PepI was especially active agains C. krusei, causing cell membrane permeability and an overproduction of Reactive Oxygen Species. Furthermore, the ability to acidify the medium was severely compromised in the treated cells. JcTI-PepI was also effective against preformed C. krusei biofilm and was non-toxic against human erythrocytes and Vero cells. Therefore, these characteristics indicate that JcTI-PepI is safe and effective against C. krusei, an intrinsically resistant strain that causes serious health problems and is often neglected, presenting a high potential for use as a new antimicrobial agent in the future.